The President’s Influence on the Formation of Lithuanian Foreign Policy: A Shift of the Power Center During Grybauskaitė’s Term - Janeliūnas, Tomas (Politologija, 2019)
This article raises the question of what role does the presidential institution hold in the Lithuanian foreign policy formation mechanism and how a particular actor (president) can change their powers in foreign policy without going beyond the functions formally defined in the Constitution. The period of President Grybauskaitė’s term and her efforts as an actor to define her role in shaping Lithuanian foreign policy are analyzed. This is assessed in the context of the activities and behavior of former Lithuanian presidents and in the context of relations with other institutions involved in foreign policy making – the Ministry of Foreign Affairs (MFA) and the Seimas in particular. This article analyzes the relationship between the actor (Grybauskaitė) and the already established structure of domestic foreign policy formation and the ability of the actor to change this structure. The analysis suggests that it is precisely because of the choices made by Grybauskaite during 2009–2019 that a relationship between the structures of foreign policy making in Lithuania has changed considerably, and that the center of power of foreign policy formation has shifted to the presidency.
Keywords: Lithuania; foreign policy; Grybauskaitė; agent vs. structure; president’s role